2022
DOI: 10.1111/ijfs.16187
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity ultrasound reduces fermentation time and improves textural properties, antioxidant activity and probiotic survival in fermented probiotic strawberry drink

Abstract: Summary This study aimed to evaluate the effect of high‐intensity ultrasound (HIUS) application with different processing times (2.5, 5, 7.5 and 10 min) on the physicochemical, rheological and textural properties, antioxidant activity (AA) and probiotic survival in strawberry‐flavoured fermented probiotic strawberry drink during storage (7°C for 28 days). The application of HIUS resulted in products with lower fermentation times, higher organic acid stability during storage and improved texture (higher firmnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, microbial viability can be increased by applying ultrasound at low levels (Rahman et al, 2023). In probiotic strawberry juice produced by applying HIUS, it was stated that 2.5 minutes of HIUS application shortened the fermentation time (3 hours), probiotic viability was better in simulated gastrointestinal conditions, probiotic viability was higher during storage, and also improved other properties of strawberry juice (Mizuta et al, 2023).…”
Section: Current Strategies To Ensure the Probiotic Viabilitymentioning
confidence: 99%
“…Thus, microbial viability can be increased by applying ultrasound at low levels (Rahman et al, 2023). In probiotic strawberry juice produced by applying HIUS, it was stated that 2.5 minutes of HIUS application shortened the fermentation time (3 hours), probiotic viability was better in simulated gastrointestinal conditions, probiotic viability was higher during storage, and also improved other properties of strawberry juice (Mizuta et al, 2023).…”
Section: Current Strategies To Ensure the Probiotic Viabilitymentioning
confidence: 99%
“…The viability of the probiotics for 28 days of storage at 7°C was examined in a study employing HIUS for processing durations of 2.5, 5, 7.5, and 10 min in the probiotic strawberry drink. The findings demonstrated that HIUS accelerates microbial viability and shortens the fermentation process in cultured probiotic strawberry drinks [ 132 ].…”
Section: Strategies To Improve the Stability Of Probiotic Bacteriamentioning
confidence: 99%